Kualitas Komunikasi dan Kreativitas Kerja sebagai Prediktor Kinerja Pegawai Sekretariat Dewan Perwakilan Rakyat Daerah" - Geomanda, Fauzan Aditya; Mariyanti, Eka; ., Hardinalis (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
The purpose of this study is to evaluate the effect of communication on employee performance at the Secretariat Office of the Regional House of Representatives (DPRD) in Padang City. The respondents consisted of 42 employees who are members of the State Civil Apparatus (ASN) at the Secretariat of the DPRD in Padang City. SPSS version 23 software was used to test the effect of communication and creativity on performance. The results showed that employee communication and creativity had a positive and significant effect on employee performance at the Padang City DPRD Secretariat Office. Furthermore, among the two variables, communication is the most dominant factor in influencing employee performance. This finding implies that it is important to improve communication in the work environment to improve employee performance at the Padang City DPRD Secretariat Office. Therefore, it is necessary to develop a communication training and development program in Padang City DPRD Secretariat to improve the effectiveness of communication between employees, management, and DPRD members and to promote creative initiatives to encourage sustainable performance growth.